Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's solve the system of linear equations step-by-step to find the ordered pair [tex]\((a, b)\)[/tex].
The system of equations given is:
[tex]\[ \left\{ \begin{aligned} -2a + 3b &= 14 \\ a - 4b &= 3 \end{aligned} \right. \][/tex]
Step 1: Solve the second equation for [tex]\(a\)[/tex] in terms of [tex]\(b\)[/tex]
Starting with the equation:
[tex]\[ a - 4b = 3 \][/tex]
We can express [tex]\(a\)[/tex] as:
[tex]\[ a = 3 + 4b \][/tex]
Step 2: Substitute [tex]\(a\)[/tex] into the first equation
Now we substitute [tex]\(a = 3 + 4b\)[/tex] into the first equation [tex]\(-2a + 3b = 14\)[/tex]:
[tex]\[ -2(3 + 4b) + 3b = 14 \][/tex]
Step 3: Simplify the equation
Distribute and combine like terms:
[tex]\[ -6 - 8b + 3b = 14 \][/tex]
[tex]\[ -6 - 5b = 14 \][/tex]
Step 4: Solve for [tex]\(b\)[/tex]
Add 6 to both sides:
[tex]\[ -5b = 20 \][/tex]
Divide by -5:
[tex]\[ b = -4 \][/tex]
Step 5: Substitute [tex]\(b\)[/tex] back into the expression for [tex]\(a\)[/tex]
Using [tex]\(a = 3 + 4b\)[/tex] and substituting [tex]\(b = -4\)[/tex]:
[tex]\[ a = 3 + 4(-4) \][/tex]
[tex]\[ a = 3 - 16 \][/tex]
[tex]\[ a = -13 \][/tex]
Thus, the solution to the system of equations is the ordered pair:
[tex]\[ (a, b) = (-13, -4) \][/tex]
Step 6: Verify the solution with the given options
Given options are:
1. [tex]\((-13, -4)\)[/tex]
2. [tex]\((-13, 4)\)[/tex]
3. [tex]\((-4, -13)\)[/tex]
4. [tex]\((-4, 13)\)[/tex]
From our solution, the correct ordered pair is [tex]\((-13, -4)\)[/tex].
Therefore, the index of the correct option is:
[tex]\[ 0 \][/tex]
The system of equations given is:
[tex]\[ \left\{ \begin{aligned} -2a + 3b &= 14 \\ a - 4b &= 3 \end{aligned} \right. \][/tex]
Step 1: Solve the second equation for [tex]\(a\)[/tex] in terms of [tex]\(b\)[/tex]
Starting with the equation:
[tex]\[ a - 4b = 3 \][/tex]
We can express [tex]\(a\)[/tex] as:
[tex]\[ a = 3 + 4b \][/tex]
Step 2: Substitute [tex]\(a\)[/tex] into the first equation
Now we substitute [tex]\(a = 3 + 4b\)[/tex] into the first equation [tex]\(-2a + 3b = 14\)[/tex]:
[tex]\[ -2(3 + 4b) + 3b = 14 \][/tex]
Step 3: Simplify the equation
Distribute and combine like terms:
[tex]\[ -6 - 8b + 3b = 14 \][/tex]
[tex]\[ -6 - 5b = 14 \][/tex]
Step 4: Solve for [tex]\(b\)[/tex]
Add 6 to both sides:
[tex]\[ -5b = 20 \][/tex]
Divide by -5:
[tex]\[ b = -4 \][/tex]
Step 5: Substitute [tex]\(b\)[/tex] back into the expression for [tex]\(a\)[/tex]
Using [tex]\(a = 3 + 4b\)[/tex] and substituting [tex]\(b = -4\)[/tex]:
[tex]\[ a = 3 + 4(-4) \][/tex]
[tex]\[ a = 3 - 16 \][/tex]
[tex]\[ a = -13 \][/tex]
Thus, the solution to the system of equations is the ordered pair:
[tex]\[ (a, b) = (-13, -4) \][/tex]
Step 6: Verify the solution with the given options
Given options are:
1. [tex]\((-13, -4)\)[/tex]
2. [tex]\((-13, 4)\)[/tex]
3. [tex]\((-4, -13)\)[/tex]
4. [tex]\((-4, 13)\)[/tex]
From our solution, the correct ordered pair is [tex]\((-13, -4)\)[/tex].
Therefore, the index of the correct option is:
[tex]\[ 0 \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.